Intentionnalité Comme Idée: Phenomenon, Between Efficacy and Analogy (Wydawnictwo Księgarnia Akademicka, 2022)
The texts collected in this volume are the result of research in the field of the pressing issues of phenomenology as a “formal,” i.e., genetic-constitutional, investigation of the sense in the scientific and philosophical dialogue to which it aspires from the beginning with Edmund Husserl. The hope of the editors is to offer the reader a textbook of quality and relevance, and perhaps a particular input to challenge and find what is given by revealing itself and/or oneself. The range of topics is very wide [...]. The choice of topics itself is extremely interesting; it makes phenomenology, broadly conceived, and its tradition, as well as its present day, a lively and passionate subject. Piotr Mróz